If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 18 + -1x = 24 Reorder the terms: 18 + 4x + -1x = 24 Combine like terms: 4x + -1x = 3x 18 + 3x = 24 Solving 18 + 3x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 3x = 24 + -18 Combine like terms: 18 + -18 = 0 0 + 3x = 24 + -18 3x = 24 + -18 Combine like terms: 24 + -18 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| V=8y^3+38y^2+9y | | 6-(5x+3)=9-7x | | -3(-7u+9)-6u=7(u-3)-4 | | 319=c-253 | | 5(2x+3)=11x-(X-15) | | -2(t+2)+5*t=6*t+11 | | -x+1=5x-8 | | 2+4x-2x^2=2-2x | | 18x+24x+12x+6x=360 | | 16-b=15 | | 3x-7y-8x-y= | | 2x-6=6x+16 | | p+p=19-1 | | 5x+3y(5x*5y)=300 | | 5x+3y(5x*5y)=200 | | 5x+3y(5x*5y)=20 | | 7m+10=31 | | 6x-5=14x+25 | | 7t+7=21 | | 2(lnx^3)-lnx+3=7 | | 3x+6y=92 | | 3k+1=40 | | 7e+3=45 | | 2(9-6)+y=12 | | 4(x+9)=3(x-8)+x | | -2(t+2)+5*t=6t+11 | | 5s+17=157 | | 7h+4=7 | | 2.4=2+0.3x | | 7p^2+6=0 | | X-4x=231 | | 2cosx=x |